2018
DOI: 10.1080/09603123.2018.1479516
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of toxic metals (Pb, Cd, Cr) in the tissues and their effects on diversification of Devario aequipinnatus populations

Abstract: Recently, momentous consideration has being given to our natural ecosystems due to toxic metals, insidious to our environment execute as pollutants to the freshwater ecosystems. The accumulations of metals were encompassed with lead, cadmium and chromium in organs of Devario aequipinnatus. Although, the microscopic scrutinization from the gill and liver of the fish species were explored, the crucial conditions of the ecosystem. The histological study plays a key role in determining the effects of pollution. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…3 Coal combustion produces acid gases, fly ash (the most crucial component of the coal combustion residuals [CCRs]), particulate matter, and potentially hazardous trace metals/elements, which have detrimental effects on humans and wildlife. 4,5 Power plants are currently the dominant emitters of mercury, acid gases, and many toxic metals in the United States. 4 Data from the United States Environmental Protection Agency (EPA) demonstrate that 62% of arsenic, 28% of nickel, 50% of mercury, 22% of chromium, 13% of NO x , and 60% of SO 2 that are toxic air pollutants come from power plants.…”
Section: Introductionmentioning
confidence: 99%
“…3 Coal combustion produces acid gases, fly ash (the most crucial component of the coal combustion residuals [CCRs]), particulate matter, and potentially hazardous trace metals/elements, which have detrimental effects on humans and wildlife. 4,5 Power plants are currently the dominant emitters of mercury, acid gases, and many toxic metals in the United States. 4 Data from the United States Environmental Protection Agency (EPA) demonstrate that 62% of arsenic, 28% of nickel, 50% of mercury, 22% of chromium, 13% of NO x , and 60% of SO 2 that are toxic air pollutants come from power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Zn concentration in the soil adjacent to the power generators in Ramadi city ranges from 17.98 to 443.73 mg/kg, with a mean value of 190.96 mg/kg. The anthropogenic sources of Zn include traffic emissions, mechanical friction of vehicles, mining, steel processing from oil pools , coal and waste combustion, and fuel emitted from generators [4,37]. Reddy et al [33] found that Zn shows higher enrichment factors for oil residue in fuel oil-based power plants .…”
Section: Results and Disscusion Concentrations Of Heavy Metalsmentioning
confidence: 99%
“…The sources of releases of heavy metals that are introduced to the soil, especially urban soils, are the industrial activities, coal and fuel burning, vehicle emissions, mining operations, fertilizers and pesticide usage, municipal solid waste disposal, and other wastes [3]. Coal and fuel combustion releases fly ash, particulate matter, and potentially dangerous heavy metals, which have harmful effects on humans and wildlife [4]. Currently, the predominant emitters of mercury, acid gases, and many toxic metals in the United States are power plants [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of industrialization, water pollution by toxic metals has become a widespread threat [4], and this, combined with the use of pesticides, fungicides, and the production of paints, paper, and welding operations, can damage the environment [5]. As a consequence, the swift implementation of rules and regulations pertaining to the health of the natural environment as well as the health of the ecosystem's dependent must be considered [6]. Therefore, natural organic components, taste, odour, and manufactured organic substances are all removed with activated carbon [7].…”
Section: Introductionmentioning
confidence: 99%